Improving the Quality of Tahfidz Learning Outcomes in Early Childhood through Teacher Management in PAUD Al-Qur’an Bekasi (International Journal of Education and Literature, 2025)
Early Childhood Education (PAUD) holds a very important role in shaping children’s character, moral values, and foundational knowledge. As an effort to support the success of education, good quality learning outcomes are required as a benchmark for children’s holistic development. In this context, educator management becomes one of the keys to improving the quality of learning outcomes. PAUD Al-Qur’an (PAUDQU) is an early childhood education institution that prioritizes Al-Qur’an education and Al-Qur’an memorization (tahfidz) as its institutional uniqueness. The findings of this research show that the educator management implemented in PAUDQU in Setu Bekasi District is quite good, as almost all elements within the scope of educator management have been carried out by the school. However, there are several obstacles found in its implementation, such as the educators’ competencies that have not been maximized, particularly in Al-Qur’an recitation (tahsin) and tahfidz, as well as the promotion, compensation, and educator assessment systems that are not yet well-structured. KIPAS EVA, an acronym for Competence Implementation Evaluation Appreciation, was developed with the expectation of being easier to remember, thus supporting the process of applying educator management in the future. This management strategy emphasizes educator planning by strengthening competencies, professional learning implementation by educators, continuous educator evaluation, and providing appreciation to increase educator motivation.